Moral Emotions - Pedagogical Perspective - Irena Barbara Przybylska; Edyta Nieduziak (Vasyl Stefanyk Precarpathian National University, 2023)
The aim of the article is to identify the status of emotions in the processes of passing judgements and taking moral decisions as well as to indicate the importance of emotional competence in moral development. In the first part of the text, we review the concept of morality, with particular reference to the emotivism of Alfred J. Ayer, Alan Gibbard's emotivism, and trends in the ethics of care by Nel Noddings as viewpoints that emphasize the affective factor. In the second part, using the concept of social, related to self-awareness and moral emotions, we argue for the role of emotions in the processes possessing moral significance. On that basis, we cautiously assume that people who have developed high emotional competence are also more morally competent. The last part is the search for pedagogical implications and justification of the thesis about the meaningful and functional relationship of emotional and moral development in the processes of upbringing. Since ethics concerns how we should live and since these areas are so much concerned with how we live, moral education ought to focus on developing moral skills (virtues), thanks to which moral feelings will guide children and adolescents.